Miss Brooks loves books! (and I don't) - Bottner, Barbara; Emberley, Michael (New York : Alfred A. Knopf, 2010)
A first-grade girl who does not like to read stubbornly resists her school librarian's efforts to convince her to love books until she finds one that might change her mind.
Keywords: Steig, William, -- 1907-2003.; Books and reading -- Juvenile fiction; Librarians -- Juvenile fiction; Schools -- Juvenile fiction